Malaysian Studies in China (2014-2024): evolving trends and multidisciplinary perspectives - Huhe, Han (Penerbit Universiti Kebangsaan Malaysia, 2024)
The year 2024 marks the 50th anniversary of the establishment of diplomatic relations between China and Malaysia. Standing at this juncture, this paper reviews the Malaysian Studies produced by Chinese academics in the past decade (2014-2024) and summarizes their research topics and disciplinary characteristics. China’s academic research on Malaysia covers a wide range of fields, including politics, diplomacy, history, and socio-culture, and there is a trend of crossover from a single discipline to a multi-disciplinary. Political studies pay close attention to Malaysia’s nation-state construction and ethnic politics; in the studies of foreign policy and relations, special attention is paid to Malaysia’s role in both regional and international geopolitics and its balancing strategies. In socio-cultural studies, research focuses on the identity and cultural integration of ethnic Chinese, which reflects insights into the changing perceptions of ethnic Chinese in the Malaysian multicultural context. The overall research is characterized as interdisciplinary and pragmatic. This paper aims to provide references for future research on both Sino-Malaysian relations and Malaysian Studies, and indirectly serve the exchange and cooperation between Chinese and Malaysian academics.